Palaeophytogeographical Patterns Across the Permian–Triassic Boundary - Nowak, Hendrik; Vérard, Christian; Kustatscher, Evelyn (Frontiers in Earth Science, 2020)
It has long been recognized that terrestrial floras underwent major and long-lasting changes during the Permian and Triassic, some of which have been attributed to the end-Permian mass extinction. However, these changes are still poorly understood with regard to the late Permian and Early Triassic. In particular, the impact that ecological disturbances around the Permian–Triassic boundary had on the composition and palaeogeographical distribution of land plant communities needs to be scrutinized. We analyse this impact based on fossil floras from across the world, covering the Wuchiapingian to Ladinian time interval. The plant assemblages are assigned to biomes representing particular environmentally controlled community types. Variations in the distribution of biomes between stages indicate shifts in the environmental parameters affecting terrestrial floras, and provide insights into population turnover dynamics. A substantial shift towards increasing seasonality and a reduction of biome diversity occurs in the earliest Triassic and stabilised throughout the Middle Triassic. However, results also show that the stratigraphically and (palaeo-)geographically unequal distribution of sampled localities constitutes an important limitation for this kind of analysis.